The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1111/j.0013-9580.2004.40903.x
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine versus Valproic Acid as First‐line Monotherapy in Newly Diagnosed Typical Absence Seizures: An Open‐label, Randomized, Parallel‐group Study

Abstract: Summary: Purpose:To compare the efficacy of lamotrigine (LTG) and valproic acid (VPA) in newly diagnosed children and adolescents with typical absence seizures.Methods: A randomized, open-label parallel-group design was used. After undergoing an awake video-EEG recording, which included one to two trials of 3 min of hyperventilation and intermittent photic stimulation, eligible patients were randomized to receive LTG or VPA. LTG was initiated at a daily dose of 0.5 mg/kg for 2 weeks in two divided doses, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
2
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 21 publications
0
74
2
2
Order By: Relevance
“…In addition, a doubleblind, placebo-controlled study suggested that LTG is effective for children with newly diagnosed absence seizures [56]. One open-label, randomized trial revealed that LTG was equivalent to VPA for the initial treatment of CAE, although equivalent seizure control was not seen for a year after beginning treatment, which was attributed to the very slow dose titration of LTG [57]. It is not uncommon for the slow titration to be a limiting factor for the use of LTG, particularly when fast seizure control is required; this may necessitate the use of a bridge medication, such as clonazepam, until a therapeutic dose is achieved.…”
Section: Gabapentinmentioning
confidence: 99%
“…In addition, a doubleblind, placebo-controlled study suggested that LTG is effective for children with newly diagnosed absence seizures [56]. One open-label, randomized trial revealed that LTG was equivalent to VPA for the initial treatment of CAE, although equivalent seizure control was not seen for a year after beginning treatment, which was attributed to the very slow dose titration of LTG [57]. It is not uncommon for the slow titration to be a limiting factor for the use of LTG, particularly when fast seizure control is required; this may necessitate the use of a bridge medication, such as clonazepam, until a therapeutic dose is achieved.…”
Section: Gabapentinmentioning
confidence: 99%
“…Valproate (VPA) is one of the most commonly used drugs for the treatment of various types of seizures, chronic neuropathic pain, bipolar disorder, and migraine headaches [13][14][15][16][17]. The antiepileptic action of VPA is believed to achieve through inhibiting the firing frequencies of high-excitable neurons by its multiple effects on GABAergic system, enzymes related to the metabolic pathways, and the activities of ion channels [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…These results support the hypotheses developed from open-label reports suggesting that lamotrigine might be effective in PGTC seizures. 9,10,15 Previous clinical trials have shown that lamotrigine is effective in the treatment of primarily generalized absence seizures 6,7 and in partial seizures in childhood. 5 Lamotrigine is also effective in the treatment of generalized seizures associated with the Lennox-Gastaut syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Lamotrigine has demonstrated efficacy from published randomized clinical trials (RCTs) for childhood partial seizures, 5 absence seizures, 6,7 and for the generalized seizures associated with Lennox-Gastaut syndrome. 8 Lamotrigine has been reported in open-label studies 9,10 and in double-blind, active-comparator RCTs to be effective in patients with newly diagnosed, previously untreated primary or secondary generalized seizures.…”
mentioning
confidence: 99%